Original Article Knowledge, Attitude, and Practice of Dentists towards Radiation Safety Procedures: A - Mardeya A A Emayof; Wfa A.A Nweh; Hawa Qaseem; Huda Mohammed (مجلة البيان العلمية, 2025)
Dentists use radiographs to diagnose, treat, and monitor dental diseases and conditions. Therefore, they must possess significant knowledge about radiation protection strategies and practice the safety standards to minimize radiation exposure and its hazardous effects. The aim: This study's purpose is to evaluate the knowledge and attitudes of dentists with respect to radiation protection standards in dental imaging, as well as their compliance with safety protocols.